Type D Personality is Associated With Disease Severity and Poor Quality of Life in Turkish Patients With Fibromyalgia Syndrome: A Cross-Sectional Study - Yeşim GARİP and Tuba GÜLER and Özgül BOZKURT TUNCER and Sinay ÖNEN (Archives of Rheumatology, 2020)
Objectives: This study aims to investigate the rate of type D personality in Turkish patients with fibromyalgia (FM) and evaluate its associations with clinical parameters of FM as well as its effects on health-related quality of life (HRQoL). Patients and methods: The study included 100 patients with FM (14 males, 86 females; mean age 34.6±7.4 years; range, 22 to 49 years) fulfilling 1990 American College of Rheumatology diagnostic criteria and 50 healthy controls (9 males, 41 females; mean age 32.6±6.5 years; range, 21 to 50 years). Type D personality was assessed using the type D scale-14 (DS-14). FM disease severity was determined by Fibromyalgia Impact Questionnaire (FIQ), functional status by Stanford Health Assessment Questionnaire (HAQ), and HRQoL by Nottingham Health Profile (NHP). Severity of pain and fatigue were measured by visual analog scale (VAS). Results: The frequency of type D personality was 33% in FM patients and 12% in controls (odds ratio=3.612, 95% confidence interval 1.398-9.333) (p=0.006). Type D FM patients scored higher in tender point count (TPC), FIQ, HAQ, VAS-pain and all NHP subgroups except energy (p<0.01). Type D personality was found to be correlated with FIQ, TPC, HAQ, VAS-pain and NHP subgroups except energy (p<0.01). Conclusion: Based on our findings, assessment of personality characteristics of patients with FM may hold the key for the treatment of the disease. Besides, a better understanding of personality-related pain in FM patients may provide a more targeted approach to pain treatment.